A copper-based catalyst and a method for preparing the same
Patent Information
- Application Number
- CN202211586594.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-10
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2042-12-10
AI Technical Summary
其中在液时质量空速为0.5-5h-1的情况下,当催化剂中纳米管长度为40-60nm时主要产物为乙醇酸甲酯,当催化剂中纳米管长度为60-300nm时主要产物为乙二醇;当催化剂中空心球粒径为80-400nm时主要产物为乙二醇,且乙二醇产率高于85%,当催化剂中空心球粒径为200-300nm时乙二醇产率高于90%,当催化剂中空心球粒径为239nm时乙二醇产率为100%,因此单位生产能力也非常低
1、本发明的催化剂具有制备方法简单、原料易得、成本低廉、环境友好的特点,且其易于实现规模化生产,符合工业化应用的要求。
Abstract
Description
Technical Field
[0001] This invention belongs to the field of oxalate hydrogenation catalyst technology, and in particular relates to a catalyst for the hydrogenation of oxalate to synthesize methyl glycol and ethylene glycol, and its preparation method. Background Technology
[0002] Methyl glycolate (MG) is an important high-value-added chemical raw material, serving as an intermediate in organic and pharmaceutical synthesis. It is produced through hydrogenation to ethylene glycol, hydrolysis to glycolic acid, oxidation to methyl glyoxylate, carbonylation to dimethyl malonate, and ammonolysis to glycine. The hydrolysis of methyl glycolate to glycolic acid, and its subsequent role as a monomer for the synthesis of polyglycolic acid (PGA), which possesses excellent biodegradability, biocompatibility, heat resistance, gas barrier properties, and mechanical strength, has attracted particular attention, demonstrating significant development value and broad market prospects. Ethylene glycol (EG) is also an important organic chemical raw material, used in the production of antifreeze and directly as a solvent. Furthermore, ethylene glycol is a crucial chemical intermediate, selectively or partially oxidized to glyoxal, glycolic acid, and methyl glycolate. It is primarily used in the reaction with terephthalic acid to produce polyethylene terephthalate (PET), a raw material for polyester fibers.
[0003] Currently, the main methods for synthesizing methyl glycolate include: the one-step method of glyoxal / ethylene glycol with methanol, the formaldehyde carbonylation-esterification synthesis method, and the hydrogenation reduction method of dimethyl oxalate. The one-step method of glyoxal with methanol has advantages such as mild reaction conditions, high feed conversion rate, and high product selectivity; however, glyoxal is highly toxic, irritating, and expensive, thus limiting its industrial production. The one-step method of ethylene glycol with methanol has advantages such as readily available feedstocks, mild reaction conditions, simple process, and environmental friendliness; however, the catalyst used in this process is sensitive to reaction conditions and has high cost, thus limiting its industrial production. Although the formaldehyde carbonylation-esterification synthesis method can generate MG with high selectivity, the reaction needs to be carried out under high temperature and pressure, and the acidity of the catalyst is highly corrosive to equipment, greatly increasing production costs and risks. Compared to other synthetic methods, the dimethyl oxalate hydrogenation reduction method is the most promising, as it involves the selective catalytic hydrogenation of dimethyl oxalate (DMO) from coal-based syngas to MG. This is a potentially green chemical route with good technical and economic advantages, better suited to my country's energy structure of "abundant coal, scarce gas, and poor oil." The reaction process produces no heavily polluting byproducts, aligning with an economical and environmentally friendly development path. Currently, the corresponding chemical technologies for this route are gradually maturing along with coal-to-ethylene glycol production. The dimethyl oxalate hydrogenation reduction method is divided into liquid-phase hydrogenation reaction systems and gas-phase hydrogenation reaction systems. Compared to homogeneous liquid-phase hydrogenation catalysts, gas-phase heterogeneous catalysts offer advantages such as milder reaction conditions, easier product separation, higher catalyst activity, and lower cost, thus attracting widespread attention from researchers.
[0004] Currently, the main research areas for DMO gas-phase selective hydrogenation to MG catalysts are silver-based and copper-based catalysts. These also include hydrogenation catalysts with transition metal phosphides as active components, some bimetallic catalytic systems with alloys as active components, and most studies modify the active component by introducing another element to influence the catalytic performance of supported copper-based catalysts. Chinese patent (CN 111437828A) provides a silver-based catalyst (Ag / NiO-XO2 / SiO2) prepared using a method that utilizes silver nitrate as the silver source, nickel nitrate as the nickel source, rare earth nitrates as the rare earth element source, tetraethyl orthosilicate as the silicon source, and introduces organic matter during the preparation process, employing a combination of sol-gel and impregnation methods. Chinese patent (CN 112206772A) provides a silver-based catalyst that uses a novel reducing agent to load silver nanoparticles onto nano-silica in an anhydrous solvent phase system. Chinese patent (CN113856700A) reports a method for preparing and applying a copper-silver bimetallic catalyst. The catalyst is prepared using a one-step sol-gel method: tetraethyl orthosilicate, ethanol, and deionized water are mixed with a metal salt solution, followed by gel aging, alkaline solution curing, washing and evaporation, and calcination reduction to gradually form a layered SiO2 structure and metal particles supported on the layered structure, yielding an Ag-Cu / SiO2 bimetallic catalyst. Chinese patent (CN 113398983A) provides a catalyst for the hydrogenation of dimethyl oxalate to methyl glycolate, using ZSM-5 molecular sieve as a support, with copper as the main active component and silver as a co-active component; wherein the copper content is 20%–50% of the catalyst mass, the silver content is 3%–15% of the catalyst mass, the ZSM-5 molecular sieve content is 40%–65% of the catalyst mass, and the silicon-to-aluminum ratio of the ZSM-5 molecular sieve is less than 500.
[0005] Although silver-based catalysts have achieved good results in the gas-phase selective hydrogenation of DMO, their high cost makes them unsuitable for industrial applications. Furthermore, silver-based catalysts exhibit poor low-temperature activity, and silver is prone to sintering at high temperatures, leading to gradual deactivation. Therefore, research has shifted towards copper-based catalysts. Adding noble metals such as Au, Ag, Pt, and Ru to Cu-based catalysts can improve the selectivity of methyl glycolate, but this method still requires the use of expensive precious metals. Based on existing literature, Cu-based catalysts remain the preferred catalysts for hydrogenation reactions, offering high hydrogenation activity, good stability, and low cost, making them most suitable for industrial applications. In the selective hydrogenation of dimethyl oxalate to methyl glycolate, most additive-modified copper-based catalysts are prepared via precipitation, and the choice of precipitant and precipitation conditions significantly affect the final catalyst performance. Chinese Patent (CN 103785408) reports a copper-silicon catalyst with multiple metal modifications prepared by co-precipitation using Cu as the main active component, alkaline silica sol as the support, and one or more non-precious metals selected from Mn, Zr, and Zn as promoters, and NaOH as the precipitant. Chinese Patent (CN105622418) provides a catalyst with Cu as the active component, SiO2 composite oxides (such as silica, SBA-15, and ZSM-5) as the support, and one or more inexpensive metals selected from Zn, Mn, Co, Ni, and Ce as promoters. The catalyst preparation method is a uniform precipitation method using ammonia water as the precipitant. Chinese Patent (CN 108499564 A) reports a catalyst with a shell distribution of promoters prepared by a two-step method of uniform precipitation and impregnation, using Cu as the main active component, and containing one or more of Zn, Mn, Mo, Al, Ni, Co, and La as promoters, with silica or silica sol as the silicon source. Chinese patent (CN111185172A) discloses a copper-based catalyst prepared from glucose via a hydrothermal method using carbon microspheres (CS) and from copper nitrate, carbon microspheres, hexadecyltrimethylammonium bromide (CTAB), and tetraethyl orthosilicate (TEOS) via an ammonia stripping method using MCu / xCS-ySiO2 carbon microsphere-silica composite support. The catalyst, with a mass percentage of 20% Cu / 1CS-1SiO2, exhibits the best catalytic activity in the hydrogenation reaction of dimethyl oxalate at a space velocity of 0.3 h⁻¹. -1 The yield of EG must be at least 90% at a space velocity of 1.5 h⁻¹. -1The yield of MG is at least 60%. Chinese patent (CN 111921547 A) reports a non-precious metal catalyst that can be synthesized using two methods. The first method is to directly synthesize a catalyst containing different components of Ni and NiP by simultaneously loading nickel salt and phosphate through co-deposition precipitation. The second method is to synthesize a catalyst intermediate containing Ni by deposition precipitation, and then synthesize a catalyst containing different components of Ni and NiP by secondary impregnation or temperature-programmed phosphate decomposition.
[0006] Copper-based catalysts exhibited good activity and selectivity in this reaction system. However, the hydrogen-ester ratio required for the dimethyl oxalate (DMO) hydrogenation reaction is high, necessitating a significant excess of hydrogen (H2 / DMO molar feed ratio typically between 80 and 200) to achieve high activity and yield. In industrial applications, however, an excessively high hydrogen-ester ratio leads to increased hydrogen circulation, raising the performance requirements of the circulating compressor and significantly increasing the production cost of the process. Chinese Patent (CN109926056A) describes a copper-based catalyst using copper nitrate as the copper source and carbon nanotubes (CNTs) as the catalyst support. The catalyst is prepared using a combination of impregnation and ultrasonication. The reaction is carried out at a pressure of 2.5 MPa, using a 10% (w / w) methanol solution of dimethyl oxalate as the raw material, with a liquid hourly space velocity (LISH) of 0.17 h⁻¹. -1 Under reaction conditions of H2 / DMO ratio of 130 and reaction temperature of 220 °C, the conversion rate of dimethyl oxalate was 83.6%, and the selectivity of methyl glycolate was 55.1%. The conversion rate of dimethyl oxalate was approximately 85%, and the selectivity of methyl glycolate was approximately 95%. Chinese Patent (CN112264078A) provides a modified boron nitride supported metal catalyst comprising a modified boron nitride support and an active component supported on the modified boron nitride support; the active component includes one of ruthenium, nickel, silver, and copper, wherein the modified boron nitride support is prepared by in-situ thermal polymerization or physical / chemical exfoliation. The reaction was carried out at a reaction pressure of 3.0 MPa, a reaction temperature of 200 °C, and a liquid hourly space velocity of 0.3 h⁻¹. -1 Under reaction conditions with a hydrogen-to-ester ratio of 100 mol / mol, the conversion rate of dimethyl oxalate was 95.4–99.9%, and the selectivity of methyl glycolate was 95.0–98.9%. Chinese Patent (CN 114558602A) provides a copper-supported porous boron nitride nanorod catalyst, comprising copper species and porous boron nitride nanorods; dimethyl oxalate is vaporized and mixed with hydrogen before entering the reaction system, with a dimethyl oxalate mass hourly space velocity (HHSV) of 0.1 h⁻¹. -1A hydrogenation reaction with a hydrogen-to-ester ratio of 120 and a pressure of 2.5 MPa yields methyl glycolate with a yield of over 95%. Chinese Patent (CN111569876A) discloses a hydrogenation catalyst using transition metal oxides (specifically CeO2, TiO2, or ZnO2) and transition metal composite oxides (specifically Ce0.5Zr0.5O2, Zn0.5Zr0.5O2, or Ti0.5Zr0.5O2) as supports, and Cu elemental or copper oxides with a copper loading controlled at 25% as the active component. When used in the direct hydrogenation of dimethyl oxalate to methyl glycolate, the reaction is carried out at a pressure of 3.0 MPa, a temperature of 240 °C, and a liquid hourly space velocity of 1.0 h⁻¹. -1 Under reaction conditions with a hydrogen-to-ester ratio of 100 mol / mol, the conversion rate of dimethyl oxalate was 91.8–98.4%, and the selectivity of methyl glycolate was 89.2–97.9%. Therefore, designing novel, highly active copper-based catalysts to achieve high selectivity and yield in the hydrogenation reaction of dimethyl oxalate even under low hydrogen-to-ester ratio conditions is key to optimizing the hydrogenation process of oxalate esters.
[0007] Current research indicates that in the hydrogenation reaction of dimethyl oxalate, to prevent catalyst deactivation, a low mass hourly space velocity (MHSV) of dimethyl oxalate is required, resulting in low production capacity for a given reactor volume. Chinese invention patent CN106563449A discloses a catalyst for the hydrogenation of oxalate ester to ethylene glycol and its preparation method. The method involves using copper nitrate and copper acetate as copper sources, alkaline silica sol as a silicon source, urea and ammonia as precipitants, and adding polyhydroxy organic compounds to prepare a Cu / SiO2 catalyst via precipitation deposition. By adding polyhydroxy organic compounds during preparation to complex with copper ions, the size and dispersion of copper species are effectively controlled. Before use, the organic matter on the catalyst is carbonized under an inert atmosphere and at a relatively high temperature, and this carbonization inhibits the aggregation of copper species, thereby improving catalyst stability. The reaction temperature is 200 ℃, the dimethyl oxalate methanol solution is 0.2 g / mL, the H2 / DMO ratio is 50 (mol / mol), and the mass hourly space velocity of dimethyl oxalate is 1.0 g (DMO / g). catUnder the reaction conditions of ·h), the selectivity of ethylene glycol is 74.0~95.3%, and the selectivity of methyl glycolate is 2.4~25.9%, resulting in very low unit production capacity. Chinese invention patent CN109248683A discloses a spherical-tube composite catalyst with hollow spheres assembled with nanotubes for oxalate hydrogenation and its preparation method. The method includes first preparing ultrapure silicon spheres with regular geometric shapes and particle sizes of 30-600 nm using a silicon source as a raw material and an alkaline agent; then preparing core-shell shaped nanomaterials with 40-300 nm length nanotubes assembled with the ultrapure silicon spheres and a copper precursor salt under alkaline conditions; finally, further hydrothermal treatment of the core-shell shaped nanomaterials under alkaline conditions to obtain hollow sphere nanomaterials assembled with 40-300 nm length nanotubes. The liquid hourly space velocity (LHSV) is 0.5-5 h⁻¹. -1 In some cases, when the nanotube length in the catalyst is 40-60 nm, the main product is methyl glycolate; when the nanotube length is 60-300 nm, the main product is ethylene glycol; when the hollow sphere diameter in the catalyst is 80-400 nm, the main product is ethylene glycol, and the ethylene glycol yield is higher than 85%; when the hollow sphere diameter is 200-300 nm, the ethylene glycol yield is higher than 90%; and when the hollow sphere diameter is 239 nm, the ethylene glycol yield is 100%. Therefore, the unit production capacity is also very low. Patent WO 2022 / 041218A1 discloses a method for preparing a copper-based catalyst. The method involves adding a suitable slow-release agent, such as urea, ferric acetate, magnesium oxalate, or ammonium carbonate, and a suitable surfactant, such as tetramethylammonium hydroxide, tetraethylammonium hydroxide, hexadecylammonium chloride, or tetramethylammonium chloride, during the preparation process to induce a hydrothermal reaction between the copper source and the silicon source. The resulting product after drying can be molded with the addition of a lubricant, such as graphite. The reaction conditions were: a reaction temperature of 185 °C, a reaction pressure of 3.0 MPa, a methanol solution containing 20% by weight dimethyl oxalate as the feedstock, a hydrogen-to-ester ratio of 80, and a liquid hourly space velocity (LHSV) of 0.6 h⁻¹. -1 Under certain reaction conditions, the DMO conversion rate can reach over 99.0%, and the ethylene glycol selectivity over 94.7%, but the production capacity is still very low. Therefore, for industrial applications, it is of great significance to change the existing mindset of controlling the hydrogenation of dimethyl oxalate to methyl glycolate and ethylene glycol under low mass hourly space velocity and low reaction temperature conditions to prevent catalyst deactivation, and thus improve the production capacity of methyl glycolate and ethylene glycol. Summary of the Invention
[0008] The purpose of this invention is to overcome the shortcomings of the prior art described above and provide a copper-based catalyst that has low preparation cost, exhibits excellent dimethyl oxalate hydrogenation activity at a low hydrogen-to-ester ratio, and has high unit production capacity of methyl glycolate and ethylene glycol. This objective can be achieved through a copper-based catalyst and its preparation method. The catalyst comprises a main active component Cu and a co-active component Ni supported on a SiO2 support, and organic copper is added to the copper precursor and organic nickel is added to the nickel precursor. By forming coke on the catalyst at a higher temperature and utilizing the coke to inhibit the aggregation of copper species, the size and dispersion of copper species can be effectively controlled, thereby improving the hydrogenation performance and stability of the catalyst.
[0009] To achieve the above-mentioned objectives, the technical solution of the present invention is as follows: A copper-based catalyst for the hydrogenation of oxalate esters, characterized in that: the catalyst comprises an active component copper, a promoter Ni, and a SiO2 support, wherein the precursor of the active component copper comprises organic copper, wherein the organic copper accounts for 0.1-15 wt.% of the total weight of the copper precursor; and the precursor of the active component nickel comprises organic nickel, wherein the organic nickel accounts for 0.1-30 wt.% of the total weight of the nickel precursor.
[0010] The copper-based catalyst for oxalate hydrogenation is characterized in that the organic copper accounts for 0.1-15 wt.% of the total weight of the copper precursor, preferably 1-10 wt.%.
[0011] The copper-based catalyst for hydrogenation of oxalate esters is characterized in that the organonitrile accounts for 0.1-30 wt.% of the total weight of the nickel precursor, preferably 1-20 wt.%.
[0012] The copper-based catalyst for oxalate hydrogenation is characterized in that the copper catalytic active component accounts for 1-30 wt.% of the total weight of the catalyst, preferably 5-20 wt.%.
[0013] The copper-based catalyst for oxalate hydrogenation is characterized in that the nickel catalytic active component accounts for 1-20 wt.% of the total weight of the catalyst, preferably 5-10 wt.%.
[0014] The method for preparing the copper-based catalyst for oxalate hydrogenation is characterized by comprising the following steps: (1) Prepare an impregnation solution by mixing one or more copper nitrates, organic copper, nickel nitrates and organic nickel, and then impregnate the silica carrier; (2) The impregnated material in step (1) is dried, calcined at high temperature and reduced.
[0015] The method for preparing the copper-based catalyst for oxalate hydrogenation, wherein the organic copper precursor in step (1) is one or more of copper succinate, copper glycinate, copper gluconate, and copper oleate.
[0016] The method for preparing the copper-based catalyst for hydrogenation of oxalate esters, wherein the organonitrile precursor in step (1) is one or more of nickel succinate, nickel glycinate, nickel gluconate, and nickel oleate.
[0017] The method for preparing the copper-based catalyst for oxalate hydrogenation, wherein in step (1) Cu in the impregnation solution 2+ and Ni 2+ The total molar concentrations were 0.5-5 mol / L and 0.5-5 mol / L, respectively.
[0018] The method for preparing the copper-based catalyst for oxalate hydrogenation includes two impregnation methods in step (1). The first method is to prepare an impregnation solution by mixing copper nitrate, organic copper, nickel nitrate and organic nickel, and then impregnate the silica support in the impregnation solution for co-impregnation. The second method is to first prepare a first impregnation solution by mixing nickel nitrate and organic nickel, then impregnate the silica support in the first impregnation solution, and then dry and calcine it at high temperature to obtain a copper-based catalyst precursor. Then, prepare a second impregnation solution by mixing copper nitrate and organic copper, and then impregnate the copper-based catalyst precursor in the second impregnation solution.
[0019] The method for preparing the copper-based catalyst for oxalate hydrogenation, wherein step (2) involves drying at 60-120°C for 1-12 hours.
[0020] The method for preparing the copper-based catalyst for oxalate hydrogenation, wherein step (2) involves high-temperature calcination at a temperature of 600-1000 °C for 1-12 hours.
[0021] The method for preparing the copper-based catalyst for hydrogenation of oxalate esters, wherein step (2) reduction is carried out in an H2 atmosphere at 100-500°C for 1-12 hours.
[0022] A method for preparing methyl glycolate and ethylene glycol by hydrogenation of oxalate ester, comprising, in the presence of the copper-based catalyst, under hydrogenation reaction conditions, a liquid hourly space velocity (LHSV) of oxalate ester of 1-10 h⁻¹. -1 Preferably 2-8 h -1 More preferably 3-6h -1 The molar ratio of hydrogen to oxalate is 5-40, more preferably 10-20; the reaction temperature is 100-300℃, more preferably 160-260℃; and the reaction pressure is 0.5-10MPa, more preferably 1.0-5.0MPa.
[0023] Compared with the prior art, the advantages and beneficial effects of the present invention are: 1. The catalyst of the present invention has the characteristics of simple preparation method, readily available raw materials, low cost, and environmental friendliness, and it is easy to achieve large-scale production, which meets the requirements of industrial application.
[0024] 2. By allowing the organic copper added to the copper precursor to form coke on the catalyst at a higher temperature, and using the coke to inhibit the aggregation of copper species, the size and dispersion of copper species can be effectively controlled, thereby improving the hydrogenation performance and stability of the catalyst.
[0025] 3. The present invention exhibits excellent activity and selectivity in the hydrogenation reaction of dimethyl oxalate to methyl glycolate and ethylene glycol at a low hydrogen-to-ester ratio (H2 / DMO = 15 (molar ratio)), which greatly reduces the required amount of hydrogen to be recycled.
[0026] 4. The copper-based catalyst of the present invention enables high unit production capacity of methyl glycolate and ethylene glycol, and has high industrial prospects and application value. Detailed Implementation
[0027] The invention will be further explained below with reference to the appendix and specific embodiments, but it should not be construed as the scope of the invention being limited to the following embodiments. Example 1
[0028] Silica was impregnated in an aqueous solution of copper nitrate, copper gluconate, nickel nitrate, and nickel gluconate, wherein Cu... 2+ and Ni 2+ The total molar concentrations were 1.32 mol / L and 1.47 mol / L, respectively. Copper gluconate accounted for 10 wt.% of the total weight of the copper precursor, and nickel gluconate accounted for 5 wt.% of the total weight of the nickel precursor. After drying at 120 °C for 12 hours, the catalyst was calcined in air at 650 °C for 4 hours to obtain Cu-Ni / SiO2 catalysts with Cu and Ni contents of 7.5 wt.% and 7.5 wt.%, respectively.
[0029] Catalyst evaluation: In this invention, the gas-phase hydrogenation reaction of dimethyl oxalate was carried out in a fixed-bed reactor with a copper-based catalyst loading of 10 mL. Reduction was performed at 300°C in a hydrogen atmosphere for 4 hours. After reduction, the temperature was lowered to the reaction temperature of 260°C, and dimethyl oxalate was mixed with pure hydrogen and introduced into the reaction tube at a hydrogen-to-ester ratio of 15. The liquid hourly space velocity (LISH) of dimethyl oxalate was 3 h⁻¹. -1 The reaction was carried out at 3 MPa. Gas chromatography was used to analyze the products, yielding the components of dimethyl oxalate (DMO), methyl glycol (MG), ethylene glycol (EG), and ethanol (EtOH). The conversion rate of dimethyl oxalate and the space-time yield (STY) of MG and EG were also analyzed. The reaction results are shown in Table 1.
[0030] Example 2 Except Cu 2+ and Ni 2+ Except for the molar concentrations of 1.32 mol / L and 0.98 mol / L, the other processes were the same as in Example 1, resulting in Cu-Ni / SiO2 catalysts with Cu and Ni contents of 7.5 wt.% and 5 wt.%, respectively.
[0031] The catalyst evaluation was the same as in Example 1, and the reaction results are shown in Table 1. Example 3
[0032] Except Cu 2+ and Ni 2+ Except for the molar concentrations of 1.76 mol / L and 0.98 mol / L, the other processes were the same as in Example 1, resulting in Cu-Ni / SiO2 catalysts with Cu and Ni contents of 10 wt.% and 5 wt.%, respectively.
[0033] The catalyst evaluation was the same as in Example 1, and the reaction results are shown in Table 1. Example 4
[0034] Except Cu 2+ and Ni 2+ Except for the molar concentrations of Cu and Ni being 0.88 mol / L and 1.47 mol / L, the other processes were the same as in Example 1, resulting in Cu-Ni / SiO2 catalysts with Cu and Ni contents of 5 wt.% and 7.5 wt.%, respectively.
[0035] The catalyst evaluation was the same as in Example 1, and the reaction results are shown in Table 1. Example 5
[0036] Except Cu 2+ and Ni 2+ Except for the molar concentrations of 0.88 mol / L and 0.98 mol / L, the other processes were the same as in Example 1, resulting in Cu-Ni / SiO2 catalysts with Cu and Ni contents of 5 wt.% and 5 wt.% respectively.
[0037] The catalyst evaluation was the same as in Example 1, and the reaction results are shown in Table 1.
[0038] Example 6 Except that copper gluconate accounts for 5 wt.% of the total weight of the copper precursor, the other processes are the same as in Example 1, and a Cu-Ni / SiO2 catalyst with Cu and Ni contents of 7.5 wt.% and 7.5 wt.% respectively is obtained.
[0039] The catalyst evaluation was the same as in Example 1, and the reaction results are shown in Table 1. Example 7
[0040] Except that copper gluconate accounts for 10 wt.% of the total weight of the copper precursor and nickel gluconate accounts for 15 wt.% of the total weight of the nickel precursor, the other processes are the same as in Example 1, and a Cu-Ni / SiO2 catalyst with Cu and Ni contents of 7.5 wt.% and 7.5 wt.% respectively is obtained.
[0041] The catalyst evaluation was the same as in Example 1, and the reaction results are shown in Table 1. Example 8
[0042] Except that copper gluconate accounts for 10 wt.% of the total weight of the copper precursor and nickel gluconate accounts for 20 wt.% of the total weight of the nickel precursor, the other processes are the same as in Example 1, and a Cu-Ni / SiO2 catalyst with Cu and Ni contents of 7.5 wt.% and 7.5 wt.% respectively is obtained.
[0043] The catalyst evaluation was the same as in Example 1, and the reaction results are shown in Table 1. Example 9
[0044] Except that nickel gluconate accounts for 1.0 wt.% of the total weight of the nickel precursor, the other processes are the same as in Example 1, and a Cu-Ni / SiO2 catalyst with Cu and Ni contents of 7.5 wt.% and 7.5 wt.% respectively is obtained.
[0045] The catalyst evaluation was the same as in Example 1, and the reaction results are shown in Table 1. Example 10
[0046] Except that nickel gluconate accounts for 10 wt.% of the total weight of the nickel precursor, the other processes are the same as in Example 1, and a Cu-Ni / SiO2 catalyst with Cu and Ni contents of 7.5 wt.% and 7.5 wt.% respectively is obtained.
[0047] The catalyst evaluation was the same as in Example 1, and the reaction results are shown in Table 1. Example 11
[0048] Silica was impregnated in an aqueous solution of nickel nitrate and nickel gluconate, wherein Ni 2+ The total molar concentration was 1.47 mol / L, and nickel gluconate accounted for 5 wt.% of the total weight of the nickel precursor. After drying at 120 °C for 12 hours, it was calcined in air at 650 °C for 4 hours to obtain a copper-based catalyst precursor with a Ni content of 7.5 wt.%. The copper-based catalyst precursor was impregnated in a solution of copper nitrate and copper gluconate, wherein Cu... 2+The total molar concentration was 1.32 mol / L, and copper gluconate accounted for 10 wt.% of the total weight of the copper precursor. After drying at 120 °C for 12 hours, the catalyst was calcined at 650 °C for 4 hours to obtain Cu-Ni / SiO2 catalyst with Cu and Ni contents of 7.5 wt.% and 7.5 wt.%, respectively.
[0049] The catalyst evaluation was the same as in Example 1, and the reaction results are shown in Table 1.
[0050] Comparative Example 1 Silica was impregnated in an aqueous solution of copper nitrate, wherein Cu 2+ The molar concentration was 1.32 mol / L. After drying at 120 °C for 12 hours, the catalyst was calcined in air at 650 °C for 4 hours to obtain a Cu / SiO2 catalyst with a Cu content of 7.5 wt.%.
[0051] The catalyst evaluation was the same as in Example 1, and the reaction results are shown in Table 1.
[0052] Comparative Example 2 Silica was impregnated in an aqueous solution of copper nitrate and nickel nitrate, wherein Cu 2+ and Ni 2+ The molar concentrations were 1.32 mol / L and 1.47 mol / L, respectively. After drying at 120 °C for 12 hours, the catalyst was calcined at 650 °C for 4 hours to obtain Cu-Ni / SiO2 catalysts with Cu and Ni contents of 7.5 wt.% and 7.5 wt.%, respectively.
[0053] The catalyst evaluation was the same as in Example 1, and the reaction results are shown in Table 1.
[0054] Comparative Example 3 Silica was impregnated in an aqueous solution of copper nitrate and copper gluconate, wherein Cu 2+ The total molar concentration was 1.32 mol / L, and copper gluconate accounted for 10 wt.% of the total weight of the copper precursor. After drying at 120 °C for 12 hours, the catalyst was calcined in air at 650 °C for 4 hours to obtain a Cu / SiO2 catalyst with a Cu content of 7.5 wt.%.
[0055] The catalyst evaluation was the same as in Example 1, and the reaction results are shown in Table 1.
[0056] Comparative Example 4 Silica was impregnated in an aqueous solution of copper nitrate and copper gluconate, wherein Cu 2+ The total molar concentration was 2.96 mol / L, and copper gluconate accounted for 30 wt.% of the total weight of the copper precursor. After drying at 120 °C for 12 hours, the catalyst was calcined in air at 500 °C for 4 hours to obtain a Cu / SiO2 catalyst with a Cu content of 15 wt.%.
[0057] The catalyst evaluation was the same as in Example 1, and the reaction results are shown in Table 1.
[0058] Table 1. Catalytic performance of copper-based catalysts in the hydrogenation of oxalate ester Example 1 98.1 2108 408 Example 2 96.5 2070 414 Example 3 95.0 2055 314 Example 4 93.0 2037 239 Example 5 92.2 2000 200 Example 6 92.5 1999 239 Example 7 97.7 2066 438 Example 8 97.8 2000 444 Example 9 89.9 1977 133 Example 10 95.7 2186 287 Example 11 96.4 1968 486 Comparison Example 1 60.0 833 643 Comparison Example 2 67.5 850 785 Comparison Example 3 88.8 1800 388 Comparison Example 4 75.0 1550 268 The copper-based catalyst of this invention has low preparation cost and, when applied to the hydrogenation reaction of dimethyl oxalate, achieves MG space-time yields and EG space-time yields of over 2000 g / (L∙h) and 400 g / (L∙h) respectively at a low hydrogen-to-ester ratio (H2 / DMO = 15 (molar ratio)). These yields are higher than those of copper catalysts without Ni (1550 g / (L∙h) and EG (268 g / (L∙h)). Furthermore, the catalyst exhibits high unit production capacity for methyl glycolate and ethylene glycol, demonstrating promising industrial application prospects.
[0059] The above description is merely a few embodiments of this application and is not intended to limit this application in any way. Although this application discloses preferred embodiments as described above, it is not intended to limit this application. Any changes or modifications made by those skilled in the art without departing from the scope of the technical solution of this application using the disclosed technical content are equivalent to equivalent implementation cases and fall within the scope of the technical solution.
Claims
1. The application of a copper-based catalyst in the hydrogenation of oxalate to prepare methyl glycolate and ethylene glycol, characterized in that: The reaction was carried out under hydrogenation conditions in the presence of the copper-based catalyst, with a liquid hourly space velocity (LISH) of oxalate of 1-10 h⁻¹. -1 The molar ratio of hydrogen to oxalate is 5-40, the reaction temperature is 100-300℃, and the reaction pressure is 0.5-10MPa. The copper-based catalyst comprises a copper active component, a nickel promoter, and a SiO2 support, wherein the copper catalytic active component accounts for 1-30 wt.% of the total catalyst weight, and the nickel catalytic active component accounts for 1-20 wt.% of the total catalyst weight. The preparation method of the copper-based catalyst includes the following steps: (1) Prepare an impregnation solution by mixing copper nitrate and copper gluconate, and nickel nitrate and nickel gluconate, and then impregnate the silica carrier; Organic copper accounts for 0.1-15 wt.% of the total weight of the copper precursor, and organic nickel accounts for 0.1-30 wt.% of the total weight of the nickel precursor. (2) The impregnated material from step (1) is dried, calcined at high temperature, and reduced; In step (2), the high-temperature calcination is carried out at a temperature of 600-1000 ℃ for 1-12 hours; In step (2), the reduction is carried out in an H2 atmosphere at 300-500 ℃ for 1-12 hours.
2. The application according to claim 1, characterized in that, Step (1) Cu in the impregnation solution 2+ and Ni 2+ The total molar concentrations were 0.5-5 mol / L and 0.5-5 mol / L, respectively; step (2) drying was performed at 60-120 ℃ for 1-12 hours.
3. The application according to claim 1, characterized in that, The copper-based catalyst contains copper catalytic active components accounting for 5-20 wt.% of the total catalyst weight; and nickel catalytic active components accounting for 5-10 wt.% of the total catalyst weight.
4. The application according to claim 1, characterized in that, In step (1) of the preparation method of copper-based catalyst, organic copper accounts for 1-10 wt.% of the total weight of copper precursor; and organic nickel accounts for 1-20 wt.% of the total weight of nickel precursor.
Citation Information
Patent Citations
Catalyst for synthesizing ethylene glycol by oxalate hydrogenation, and preparation method and application method of catalyst
CN106563449A
Catalyst for use in synthesis process of methyl glycolate as well as preparation method and application of catalyst
CN108499564A
Bulb composite catalyst for hydrogenation of oxalate and preparation method thereof
CN109248683A
Catalyst taking carbon nano tube as carrier as well as preparation method and application thereof
CN109926056A
High-activity catalyst for dimethyl oxalate hydrogenation and preparation method of the high-activity catalyst
CN111185172A